Pengembangan Profesionalisme Guru Melalui In House Training - Baharuddin Baharuddin; Rabial Kanada (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
The development of teacher professionalism is in the spotlight of today's world. This is due to the changing paradigm of education as a consequence of the development of the times and challenges of education. This paper aims to provide an overview and understanding of the importance of changing old patterns in developing a teacher's professional. Monotonous and centralistic coaching and training is no longer relevant to use for the present. One of the new methods that deserve to be practiced as a form of teacher professional development is through in-house training. A method that puts forward collaborative, contextual and constructivist approaches so that the value of its benefits is more clearly felt by teachers.